Analysis of the conductive properties and structural surroundings of sodium ions in GeGaSbS sulfur glass system. (July 2021) - Shan, Haiyang; Jiao, Qing; Zhang, Yeting; Ma, Baochen; Dong, Pingping; Xu, Tiefeng
Abstract: Sodium-ion-doped glass ceramics may potentially be used as solid electrolytes. In this study, a novel sulfide-based sodium-ion electrolyte, namely Ga4 Ge12 Sb64 S128 – x NaI ( x  = 5–25), with an optimized network structure and good physical properties, has been prepared by a melting and milling route. The properties of this novel electrolyte have been investigated by Raman spectroscopy, differential scanning calorimetry, X-ray diffraction analysis, and electrochemical methods. The ionic conductivity of the conductors at room temperature proved to be superior to that of the GaSbS-NaI glass system and increased to the order of 10 −5  S/cm. The differentiation in conductivity originated from microstructural changes in ion channels and crystal growth. The optimal glass composition for harnessing the characteristics of sulfide sodium-ion conductor materials was designed by extrapolation of the analytical results. Highlights: The influence of Ge doping on the microstructure and properties of Ga–Sb–S ternary solid electrolyte has been investigated. The NaI content in Ga4 Ge12 Sb64 S128 systems influences the proportions of crystalline and amorphous states. The [GaS4- x I x ] units are partly replaced by [GeS4- x I x ] as the main junction of channels, which improves the ionic conductivity.